Phytoextraction of risk elements by willow and poplar trees - Kacálková, Lada; Tlustoš, Pavel; Száková, Jiřina (International journal of phytoremediation, 2015)
To characterize the phytoextraction efficiency of two clones of willow trees (Salix x smithiana Willd., Salix rubens) and two clones of poplar trees (Populus nigra x maximowiczii, Populus nigra Wolterson) were planted in contaminated soil (0.4-2.0 mg Cd.kg(-1), 78-313 mg Zn.kg(-1), 21.3-118 mg Cu.kg(-1)). Field experiment was carried out in Czech Republic. The study investigated their ability to accumulate heavy metals (Cd, Zn, and Cu) in harvestable plant parts. The poplars produced higher amount of biomass than willows. Both Salix clones accumulated higher amount of Cd, Zn and Cu in their biomass (maximum 6.8 mg Cd.kg(-1), 909 mg Zn.kg(-1), and 17.7 mg Cu.kg(-1)) compared to Populus clones (maximum 2.06 mg Cd.kg(-1), 463 mg Zn.kg(-1), and 11.8 mg Cu.kg(-1)). There were no significant differences between clones of individual species. BCs for Cd and Zn were greater than 1 (the highest in willow leaves). BCs values of Cu were very low. These results indicate that Salix is more suitable plant for phytoextraction of Cd and Zn than Populus. The Cu phytoextraction potential of Salix and Populus trees was not confirmed in this experiment due to low soil availability of this element.
Keywords: Trees; biodegradace; Copper; stromy; Soil Pollutants; látky znečišťující půdu; contaminated soil; willow; zinc; Zinc; phytoextraction; zinek; Biodegradation, Environmental; měď; Salix; Cadmium; Environmental Restoration and Remediation; copper; cadmium; kadmium; regenerace a remediace životního prostředí; Populus; poplar